Rapid and highly sensitive detection of extracellular and intracellular H2S by an azide-functionalized Al(iii)-based metal–organic framework. Issue 38 (18th September 2017) - Nandi, Soutick; Reinsch, Helge; Banesh, Sooram; Stock, Norbert; Trivedi, Vishal; Biswas, Shyam
Abstract : Fast and highly sensitive sensing of both extracellular and intracellular H2 S by an Al(iii )-based CAU-10-N3 MOF is presented. Abstract : A new, azide-functionalized Al(iii )-based metal–organic framework (MOF) denoted as CAU-10-N3 (1, CAU = Christian-Albrechts-University) and consisting of the 5-azido-isophthalic acid (H2 IPA-N3 ) ligand was employed as a reaction-based fluorescent turn-on probe for the detection of H2 S. The activated compound (1′ ) showed fast, selective and highly sensitive sensing properties for extracellular H2 S in HEPES buffer (10 mM, pH = 7.4). The material retained its high selectivity even in the presence of possibly competing biological species. The limit of detection of1′ for H2 S is 2.65 μM, which is lower than the earlier reports on MOFs for H2 S sensing. The material displayed a short response time (420 s) and a significant increase (20-fold and 26-fold after 1 and 7 min of addition of Na2 S, respectively) in the fluorescence intensity towards H2 S. Macrophage cells loaded with probe1′ exhibited blue fluorescence with a response time of 15 min after Na2 S addition, indicating the suitability of the probe for intracellular H2 S detection. Moreover, CAU-10-N3 featured excellent detection performance (quick response and 32-fold increment in fluorescence intensity after 7 min of Na2 S addition) in water. Hence, it can be utilized to regulate the H2 S level in aqueous samples collected from the environment.